Noise reduction effect of computed tomography by image summation method (fused CT): Phantom study. (December 2020) - Kobayashi, Tomoya; Yoshida, Masahiro; Numano, Tomokazu; Shiotani, Seiji; Saitou, Hajime; Tashiro, Kazuya; Someya, Satoka; Kaga, Kazunori; Miyamoto, Katsumi; Hayakawa, Hideyuki
Highlights: Noise and sharpness of CT by image summation method (fused CT) was evaluated with two types of phantom. Increased number of image summation in fused CT reduces standard deviation and noise power spectrum. Noise reduction effect of fused CT becomes small after 10 times image summation. Increased number of image summation in fused CT does not change modulation transfer function. Abstract: We measured standard deviation (SD), noise power spectrum (NPS), and modulation transfer function (MTF) of computed tomography obtained by image summation method (fused CT) using phantoms. SDs, NPSs and MTFs of fused CT up to 25 times summation were calculated. Increased number of image summation reduced SD and NPS, although the effect became small after 10 times summation. MTF remained the same regardless of the number of summation. Fused CT is effective in reducing noise.